Pengembangan Sektor Ekonomi Daerah Tertinggal di Provinsi Kalimantan Barat - Supianto, Supianto; Urep, Silvester Ansel; Putra, Windhu (Fakultas Ekonomi dan Bisnis, UNTAN, 2017)
This study aims to determine the contributions and and analize the leading sectors and changes of economics structure which can be used as information of economics development in undeveloped regions in West Kalimantan. The results show that agricultures, forestries and fisheries sectors are the economics sectors with the highest average contribution rates for all underdeveloped regions in Kalimantan Barat Province; while electricity and gas procurement sectors become economics sectors with the smallest contribution average in the formation of Gross Regional Domestic Product (GRDP) of all underdeveloped regions. The real estates sector and the health services sector and social activities are the leading sectors as well as the agricultures, forestries and fisheries sectors and the mining and quarrying sectors into potential sectors to be developed into the leading sectors in disadvantaged areas. This study also shows that there has been a structural transformation of the economy from the primary sector to the tertiary and secondary sectors marked by the decline in the role of the primary sector and the increasing role of the tertiary and secondary sectors to the formation of GRDP and the absorption of manpower in all the underdeveloped regions in West Kalimantan Province.